2013
DOI: 10.1002/jgrb.50268
|View full text |Cite
|
Sign up to set email alerts
|

Are deep‐ocean‐generated surface‐wave microseisms observed on land?

Abstract: [1] Recent studies attribute land double-frequency (DF) microseism observations to deep water generation. Here we show that near-coastal generation is generally the dominant source region. This determination is based on observations at land and ocean seismic stations, buoys, gravity-wave hindcasts, and on beamforming results from continental seismic arrays. Interactions between opposing ocean wave components generate a pressure excitation pulse at twice the ocean wave frequency that excites pseudo-Rayleigh (pR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 60 publications
4
68
0
Order By: Relevance
“…Observed microseismic noise has been explained by a physical process based on a nonlinear wave-wave interaction mechanism (Longuet-Higgins, 1950;Hasselmann, 1963). Several studies tried to locate the noise sources at sea (e.g., Bromirski and Duennebier, 2002;Bromirski et al, 2005Bromirski et al, , 2013Tanimoto, 2007), but only recently a wave-wave interaction model has been applied to predict the amplitude of microseismic noise and compare it with the ones observed by on-land seismometers (Kedar et al, 2008;Ardhuin et al, 2011). In addition to global sources of noise, such as long-wavelength ocean waves that also affect the remotest land sites, there are other more local-and/or site-dependent sources that determine the signal-to-noise level, therefore limiting the possibility to efficiently detect waveforms from seismic events.…”
Section: Introductionmentioning
confidence: 99%
“…Observed microseismic noise has been explained by a physical process based on a nonlinear wave-wave interaction mechanism (Longuet-Higgins, 1950;Hasselmann, 1963). Several studies tried to locate the noise sources at sea (e.g., Bromirski and Duennebier, 2002;Bromirski et al, 2005Bromirski et al, , 2013Tanimoto, 2007), but only recently a wave-wave interaction model has been applied to predict the amplitude of microseismic noise and compare it with the ones observed by on-land seismometers (Kedar et al, 2008;Ardhuin et al, 2011). In addition to global sources of noise, such as long-wavelength ocean waves that also affect the remotest land sites, there are other more local-and/or site-dependent sources that determine the signal-to-noise level, therefore limiting the possibility to efficiently detect waveforms from seismic events.…”
Section: Introductionmentioning
confidence: 99%
“…Most DF microseisms observed on land are generated in coastal regions by ocean wave activity and propagate into the continent primarily as Rayleigh waves [ Haubrich and McCamy , ; Cessaro , ; Friedrich et al , ; Schimmel et al , ; Bromirski et al , ]. However, it has also been reported that DF microseisms can be generated by distant mid‐ocean storms and propagate as P waves [ Haubrich and McCamy , ; Lacoss et al , ; Vinnik , ; Gerstoft et al , ; Koper et al , ; Sheen , ] and even as P P and P K P phases [ Gerstoft et al , ; Koper and de Foy , ; Koper et al , ; Landes et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…SM noise sources have been located in near-coastal shallow waters (e.g. Bromirski et al 2013), related to coastal swell reflections interacting with the incident swell (e.g. Bromirski & Duennebier 2002) and also in deep waters (e.g.…”
Section: Introductionmentioning
confidence: 99%